The Intent of Chile S Trade Policy: Adjustments Through and Pragmatism in Legislative Measures, 1850-1914 [Los Designios de la Política Comercial de Chile: Adecuaciones Mediante y Pragmatismo en Las Medidas Legislativas, 1850-1914] - Dingemans-Calderon, A (Instituto de Investigaciones Dr. Jose Maria Luis Mora, 2022)
Contrary to the common historiographical approach, this article does not assume doctrinal similarity as the main driver of trade policy. It proposes instead to consider it as the result of a political process that involves multiple interests. Particularly Chile s trade policy (1850-1914), based on its Customs Ordinances, has been considered a faithful reflection of the economic doctrines of the time. However, this article proposes to extend the empirical analysis to the different policy measures, such as laws and decrees, emphasizing their ex ante (de iure) rather than ex post (effective) tariff structure. The results suggest a compensatory use of tariffs that led to a persistent reduction in tariffs, independent of the prevailing doctrine in the ordinance. Its “intents” were therefore more pragmatic than doctrinal. © 2022 Instituto de Investigaciones Dr. Jose Maria Luis Mora. All rights reserved.